Nicotinamide Mononucleotide Alleviates Osteoblast Senescence Induction and Promotes Bone Healing in Osteoporotic Mice. Issue 2 (29th August 2022) - Lu, ZuFu; Jiang, Liting; Lesani, Pooria; Zhang, WenJie; Li, Ning; Luo, Danyang; Li, Yusi; Ye, Yulin; Bian, Ji; Wang, Guocheng; Dunstan, Colin R; Jiang, XinQuan; et al.
Abstract: Combating the accumulated senescent cells and the healing of osteoporotic bone fractures in the older remains a significant challenge. Nicotinamide mononucleotide (NMN), a precursor of NAD +, is an excellent candidate for mitigating aging-related disorders. However, it is unknown if NMN can alleviate senescent cell induction and enhance osteoporotic bone fracture healing. Here we show that NMN treatment partially reverses the effects of tumor necrosis factor-alpha (TNF-α) on human primary osteoblasts (HOBs): senescent cell induction, diminished osteogenic differentiation ability, and intracellular NAD + and NADH levels. Mechanistically, NMN restores the mitochondrial dysfunction in HOBs induced by TNF-α evidenced by increased mitochondrial membrane potential and reduced reactive oxidative species and mitochondrial mass. NMN also increases mitophagy activity by down-regulating P62 expression and up-regulating light chain 3B-II protein expression. In addition, the cell senescence protective effects of NMN on HOBs are mitigated by a mitophagy inhibitor (Bafilomycin A1). In vivo, NMN supplementation attenuates senescent cell induction in growth plates, partially prevents osteoporosis in an ovariectomized mouse model, and accelerates bone healing in osteoporotic mice. We conclude that NMN can be a novel and promising therapeutic candidate to enhance bone fracture healing capacity in the older.